1997
DOI: 10.1002/abio.370170105
|View full text |Cite
|
Sign up to set email alerts
|

Selection of yeast strain and fermentation conditions for high‐yield ethanol production from lactose and concentrated whey

Abstract: A total of 65 yeast strains were screened for their ability to grow and ferment lactose in a standard DURHAM tube test at 30 "C. Based on the kinetic parameters for lactose and whey lactose fermentations in shake flask cultures, the strain Condidu pseudotropicdis 65 was chosen for further studies. Some of the cultural parameters affecting ethanolic fermentations on lactose were standardized. At an initial lactose concentration of 1oOLI20 g/l in the medium containing concentrated whey or lactose, at 40 OC and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…Among the works on whey fermentation by natural lactose-fermenting yeasts, a few report higher ethanol titers but considerably lower productivities [9,22] compared to this work. Conversely, some report higher productivity but lower ethanol titer [11,12,17,46]. Only two papers report simultaneously higher ethanol titer and higher productivity [20,43] than obtained in this work.…”
Section: Repeated-batch Whey Fermentations In An Air-lift Bioreactor contrasting
confidence: 79%
See 2 more Smart Citations
“…Among the works on whey fermentation by natural lactose-fermenting yeasts, a few report higher ethanol titers but considerably lower productivities [9,22] compared to this work. Conversely, some report higher productivity but lower ethanol titer [11,12,17,46]. Only two papers report simultaneously higher ethanol titer and higher productivity [20,43] than obtained in this work.…”
Section: Repeated-batch Whey Fermentations In An Air-lift Bioreactor contrasting
confidence: 79%
“…Accordingly, several authors have reported substrate inhibition effects on ethanol production and/or yeast growth, particularly at high initial lactose concentrations (150-200 g/l), for Kluyveromyces spp. [20,[35][36][37]43] and Candida pseudotropicalis [11,46]. The high ash content (particularly sodium and potassium) in concentrated whey has also been reported to inhibit yeast growth and ethanol formation by Kluyveromyces spp.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the yield obtained with the NRRL‐Y1140 strain seems high for a respiratory yeast, the distribution between respiratory and fermentative metabolism in wild‐type K. lactis is dependent on oxygen availability (González‐Siso et al ., ; Guimarães et al ., ) and low levels of oxygen in these cultures favour fermentation. Similar ethanol yields in whey than those reached by the NRRL‐Y1140 strain in this work were obtained by other authors in fermentative conditions with other Kluyveromyces strains (Szczodrak et al ., ; Guimarães et al ., ).…”
Section: Resultsmentioning
confidence: 98%